“World Nationality” by Eyes of it’s Critics (Five Arguments against “Saturated” Cosmopolitism of M. Nussbaum) - Sergey Vladimirovich Akopov (Управленческое консультирование, 2018)
The objective of this article is the review and critique of the analysis of global citizenship through the lens of political philosophy of communitarianism, neo-Marxist world-system analysis, liberal nationalism and traditionalism.